Multicultural awareness and practice among language teachers - Muhamad, Ainon Jariah; Othman, Khairiah; Engku Ibrahim, Engku Haliza; Esa, Zaleha; Abdul Malik, Faridah (2017)
The changing demographics of higher education due to internationalization has made it incumbent upon educators to promote as well as create multicultural learning environments to meet the challenges of teaching in culturally diverse settings. Studies have shown that teachers’ awareness of multiculturalism will have a direct effect on students’ behaviour and academic outcomes. It is crucial for teachers to examine their own knowledge and teaching behavior, the values, as well as perspectives of the cultural groups who are the subjects of their teaching, and be able to transfer that knowledge into effective instruction. The objectives of this study are thus to ascertain whether language teachers are aware of what multiculturalism is and what it entails and to investigate their multicultural practices in dealing with a very culturally diverse population of students. The quantitative approach was employed where questionnaires were administered to 40 in-service language teachers of an international higher institution of learning. Findings revealed that that there is to a great extent an awareness of multiculturalism among the staff. There is also a positive indication of integrating multiculturalism in their language classrooms.